THE CONCEPT OF "POLITENESS" IN ENGLISH LINGUISTICS (Conferencea, 2023)
This article is devoted to the interpretation of "politeness" in English linguistics. The article contains information about the founders of the theory of politeness and various theoretical views. According to the purpose of the article, the role of the category "politeness" in intercultural communication is shown and linguistically analyzed on the example of English linguistics.